2016
DOI: 10.1089/thy.2016.0212
|View full text |Cite
|
Sign up to set email alerts
|

The Ethical Implications of the Reclassification of Noninvasive Follicular Variant Papillary Thyroid Carcinoma

Abstract: Informing patients with a previous diagnosis of EFVPTC that the disease has been reclassified as benign is expected to have a dramatic effect on their surveillance needs and to alleviate the psychological impact of living with a diagnosis of cancer. It is important to re-evaluate the pathologic slides of those patients at risk to ensure that the invasive nature of the tumor is comprehensively evaluated before notifying a patient of a change in diagnosis. The availability of the entire tumor for evaluation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…According to the National Comprehensive Cancer Network (NCCN), post‐thyroidectomy follow‐up for patients with PTC includes ultrasonographic surveillance and testing of blood levels of thyroglobulin, anti‐thyroglobulin antibodies and thyrotrophin at 6 and 12 months postoperatively and then annually . It is expected that a de‐escalation in surveillance would reduce costs further . Introduction of the NIFTP nomenclature may have also financial implications for patients.…”
Section: The Impact Of the Niftp Paradigm Shiftmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the National Comprehensive Cancer Network (NCCN), post‐thyroidectomy follow‐up for patients with PTC includes ultrasonographic surveillance and testing of blood levels of thyroglobulin, anti‐thyroglobulin antibodies and thyrotrophin at 6 and 12 months postoperatively and then annually . It is expected that a de‐escalation in surveillance would reduce costs further . Introduction of the NIFTP nomenclature may have also financial implications for patients.…”
Section: The Impact Of the Niftp Paradigm Shiftmentioning
confidence: 99%
“…found that approximately a third of patients with differentiated non‐medullary thyroid carcinoma reported distress levels indicative of clinically relevant distress. On the basis of the financial and psychological consequences of a thyroid cancer diagnosis, some have advocated informing patients with a previous diagnosis of non‐invasive encapsulated FVPTC that the disease has been reclassified and is no longer designated as carcinoma; however, it seems unlikely that this approach is practically feasible.…”
Section: The Impact Of the Niftp Paradigm Shiftmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was shown that there was significant interobserver variability in the FVPTC diagnosis, largely due to differences in what was considered sufficient PTC nuclear features [21][22][23]. In the few studies that have retrospectively evaluated the number of thyroid carcinomas that would now be classified as NIFTP, NIFTP accounted for 9-25% of carcinomas [8][9][10]. More studies are needed in order to better estimate the impact of NIFTP, both at academic centers and in community practices, in different regions of the USA, and in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted prior to the characterization of NIFTP; however, it is likely that a significant subset of the tumors would represent NIFTPs. In the few studies that have evaluated the impact of NIFTP on thyroid carcinoma diagnoses, tumors previously diagnosed as noninvasive FVPTC (now NIFTP) accounted for between 9 and 25% of thyroid carcinomas [3,[8][9][10]. Although the introduction of the NIFTP nomenclature was aimed to reduce the overtreatment of an indolent thyroid tumor and spare patients the psychological burden of a cancer diagnosis [1,11], the introduction of NIFTP will have additional consequences.…”
Section: Introductionmentioning
confidence: 99%